Planetary Health: A Framework for Expanding the Boundaries of Global Health Law - Marlies Hesselman; Benjamin Mason Meier; Judith Bueno De Mesquita; Luciano Bottini Filho; Tsung-Ling Lee; Kriti Sharma; Sam Halabi; Monique van Cauwenberghe; Dominique Mollet; Gian Luca Burci (Journal of Law, Medicine & Ethics, 2026)
Abstract This article examines how the emerging framework of “Planetary Health” challenges us to reconsider the role and boundaries of global health law, for example by engaging with systems thinking, eco-centric perspectives, Indigenous knowledge, and newly emerging human rights. How does planetary health inspire novel thinking or new approaches around the conceptualization, design, implementation and/or interpretation of global health law and health-related rights, aiming to protect vital ecological foundations or determinants of health?